Pengaruh Kredibilitas dan Gaya Komunikasi Rania Yamin terhadap Minat Berkain Followers Instagram @raniaayamin - Salsabiila Mahdiyyah; Christina Tri Hendriyani (Universitas Sebelas Maret (UNS), 2025)
The purpose of the study was to determine the effect of Rania Yamin's credibility and communication style on the interest in berkain of Instagram followers @raniaayamin. Berkain is a movement that encourages people, to wear Indonesia’s traditional patterned fabrics in their daily activities by combining them with modern clothing and sharing them through social media posts. The phenomenon of the berkain trend that is back in full swing on social media, especially among young people, is inseparable from the role of influencers who have enlivened this trend. Rania Yamin is one of the influencers who consistently wears berkain on her social media accounts. This research uses explanatory quantitative research methods with survey techniques through questionnaires distributed to 100 respondents aged 16-34 who are active followers of the @raniaayamin Instagram account. The data analysis techniques used include validity test, reliability test, multiple linear regression analysis, partial test, simultaneous test, and coefficient of determination test which are processed with the help of the SPSS 26. The results showed that both source credibility and communication style had a partial and simultaneous effect on interest in berkain. This research refers to the Elaboration likelihood model theory to explain if there are two paths in the process of receiving persuasive messages, namely the central and peripheral routes. Communication style variables have a greater influence than source credibility with t count > t table of 9,760 > 1,984. The source credibility variable also has a positive effect with t count 2,178 > 1,984. Both have a significant effect simultaneously with t count > t table of 131,170 > 3,09. Based on the results of the coefficient of determination, it can be concluded that the ability of the independent variables of credibility (X1) and communication style (X2) in this study affects the dependent variable of interest in berkain (Y) by 72.4% while 27.6% is influenced by other variables outside the study. Based on the analysis of per-variable data and indicators, it can be concluded that the audience processes messages through both peripheral and central routes.